The Concept of Total Leadership of Islamic Boarding Schools in KH Abdullah Syukri Zarkasyi’s Perspective (Case Study in Modern Islamic Boarding School Darussalam Gontor 1985-2020) - Awaluddin Faj; Didin Hafidhuddinb; Hendri Tanjung; Budi Handrianto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The existence of Kiai as a leader of Islamic boarding schools are very urgent and vital, because the success of Islamic boarding schools is largely from leadership factor of Kiai, so that he is the main pillar of leadership in realizing the progress of Islamic boarding schools, then KH Abdullah Syukri Zarkasyi saw that, leadership is the source of the benefit and problems of mankind. Even the problems of the people until now are about leadership. The aim of this study is to find out the Total Leadership Concept of Islamic Boarding Schools in KH Abdullah Syukri Zarkasyi’s Perspective who has had extraordinary experience in developing Darussalam Gontor Modern Islamic Boarding School from 1985-2020. In this study, researchers used qualitative research with a phenomenological approach, with field exploration and a theoretical orientation or theoretical perspective with a phenomenological approach. From the results of this study, it indicates that the concept of total leadership of Islamic Boarding School in KH Abdullah Syukri Zarksyi’s perspective is Priority, Focus and above personal interests, a leader must be willing and able to devote his time and thoughts to the interests of the Islamic boarding school above personal and family interests. Total leadership must be able to identify and solve all problems and solve them, either independently or delegated to the institution, he is a visionary leader, initiator, anticipatory inspirational, and has an analytical mind on every problem